Effects of pathogen reduction systems on platelet microRNAs, mRNAs, activation, and function. (18th April 2014) - Osman, Abdimajid; Hitzler, Walter E.; Meyer, Claudius U.; Landry, Patricia; Corduan, Aurélie; Laffont, Benoit; Boilard, Eric; Hellstern, Peter; Vamvakas, Eleftherios C.; Provost, Patrick
Abstract: Pathogen reduction (PR) systems for platelets, based on chemically induced cross-linking and inactivation of nucleic acids, potentially prevent transfusion transmission of infectious agents, but can increase clinically significant bleeding in some clinical studies. Here, we documented the effects of PR systems on microRNA and mRNA levels of platelets stored in the blood bank, and assessed their impact on platelet activation and function. Unlike platelets subjected to gamma irradiation or stored in additive solution, platelets treated with Intercept (amotosalen + ultraviolet-A [UVA] light) exhibited significantly reduced levels of 6 of the 11 microRNAs, and 2 of the 3 anti-apoptotic mRNAs ( Bcl-xl and Clusterin ) that we monitored, compared with platelets stored in plasma. Mirasol (riboflavin + UVB light) treatment of platelets did not produce these effects. PR neither affected platelet microRNA synthesis or function nor induced cross-linking of microRNA-sized endogenous platelet RNA species. However, the reduction in the platelet microRNA levels induced by Intercept correlated with the platelet activation ( p  < 0.05) and an impaired platelet aggregation response to ADP ( p  < 0.05). These results suggest that Intercept treatment may induce platelet activation, resulting in the release of microRNAs and mRNAs from platelets. The clinical implications of this reduction in platelet nucleic acids secondary to Intercept remain to be established.